Roma Identity and Ritual in the Classroom The Institutional Embeddedness of Ethnicity - Obrovská, Jana (Springer International Publishing, 2018)
This book addresses the dynamics of interethnic relationships in ethnically mixed classrooms in the Czech Republic. The classroom is a space in which the boundaries and meanings of facets of identity such as ethnicity, class and gender are negotiated on a daily basis: using rich ethnographic data, the author grounds the analysis in a novel theoretical framework which uses the traditional concept of ritual to examine peer cultures. Highlighting the perspectives of the students themselves, their own peer cultures and the agency of the minority youth present in the classroom, the book reinforces the idea that the dynamics of peer culture can be the scene for successful peer inclusion strategies as well as a stage for the reproduction of inequalities. The author offers a rich array of data from post-socialist classrooms, which are almost invisible in the dominant debates surrounding ethnicity. This revelatory book will be of interest and value to students and scholars of social anthropology, the sociology of education and race and ethnicity in education, as well as practitioners working with minority youth.